PERCEPTION OF THE ROLE OF ANIMAL HUSBANDRY IN THE DEVELOPMENT OF GERDARSI BEACH AS A TOURIST ATTRACTION - Fredrik M. Manaha; Michel J. Matatula; Heriyanus Jesayas (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
This study aims to describe the perception and participation of farmers, farmers community of Klis Village - Nyama Hamlet in the development of gerdarsi beach attractions. Research method is descriptive qualitative. Using interview data collection techniques, observation and documentation. The results of this study showed the form of participation of farmers community in the development of gerdarsi beach tourism attraction is 1). Donate picket. 2). Keep the location security. 3). Maintaining the beauty of the location. 4). Art. The participation rate of the community of farmers in supporting the development, implementation and utilization. Thus it can be said that the community of farmers has participated well in the process of development and development of gerdarsi beach attractions.